2011
DOI: 10.1111/j.1469-0691.2010.03225.x
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-lactamases among Enterobacteriaceae from routine samples in an Italian tertiary-care hospital and long-term care facilities during 2008

Abstract: The emergence of metallo-β-lactamase (MBL)-producing Enterobacteriaceae is a serious public health concern. Producers have been repeatedly isolated from patients and long-term care facility (LTCF) residents around Bolzano, and we sought to assess their prevalence and clinical impact. All routine Enterobacteriaceae isolates from a Bolzano tertiary-care hospital and associated long-term care facilities in 2008 (n = 5500) were screened for MBLs, with case details reviewed for the source patients. In total, 36 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…Similarly, 80% (44/55) of ESBL producing E. coli isolates from screening samples of long-term care facility residents in 2008 had CTX-M group 1 enzymes; sequencing identifi ed them as CTX-M 15, except for one isolate with CTX-M-1 [14]. Th e three detected CTX-M group 9 enzymes from Bolzano in this study also confi rmed previous fi ndings [14,22]. Single E. coli isolates in Innsbruck and Bolzano with CTX-M group 2 enzymes isolated from patients one originating from an unknown source and the other perhaps from Romania confi rm the threat of importation of still rare CTX-M types in our region [23].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, 80% (44/55) of ESBL producing E. coli isolates from screening samples of long-term care facility residents in 2008 had CTX-M group 1 enzymes; sequencing identifi ed them as CTX-M 15, except for one isolate with CTX-M-1 [14]. Th e three detected CTX-M group 9 enzymes from Bolzano in this study also confi rmed previous fi ndings [14,22]. Single E. coli isolates in Innsbruck and Bolzano with CTX-M group 2 enzymes isolated from patients one originating from an unknown source and the other perhaps from Romania confi rm the threat of importation of still rare CTX-M types in our region [23].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in our region, colistin seems to be the only reliable antibiotic alternative for severe infections with VIMproducing members of the Enterobacteriaceae, but its use is limited because of adverse toxicity effects. In addition, there are several reports of resistance to colistin from other countries (Livermore et al, 2011;Meletis et al, 2011). PFGE revealed that the spread of VIM-1-producing E. cloacae in Tyrol is mainly due to dissemination of one genotype.…”
Section: Carbapenemase-producing Enterobacter Cloacae In Tyrolmentioning
confidence: 98%
“…Carbapenem resistance in clinical isolates of E. cloacae is unusual but has been described in strains with porin alterations combined with the hyperproduction of chromosomal cephalosporinase (Lee et al, 1991), and in strains producing class A carbapenem-hydrolysing nonMBLs (Rasmussen et al, 1996). MBLs have been reported in clinical isolates of E. cloacae from various geographical areas (Aschbacher et al, 2011;Falcone et al, 2009;Queenan & Bush, 2007;Tato et al, 2007;Treviño et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The other case, a different microorganism was isolated after third BL session. The pathogen was Klebsiella oxytoca, a metallo-beta-lactamase-producing Enterobacteriaceae (1) . This microorganism can cause various infectious complications in both healthy and immunocompromised subjects, such as port central venous catheter-associated bloodstream infection (13) , spontaneous peritonitis (16) and malignant external otitis (6) , and was recently described as the causative agent of antibiotic-associated hemorrhagic colitis (8) .…”
Section: Discussionmentioning
confidence: 99%
“…1 worldwide to arrest bleeding from gastric varices and differs from conventional sclerosants because it polymerizes within seconds on contact with aqueous media (3) . Furthermore, studies have demonstrated the usefulness of CY injection for the treatment of bleeding or no bleeding esophageal varices, especially in ChildPugh C cirrhotic patients (11) .…”
Section: Introductionmentioning
confidence: 99%